Students’ health behaviors – own research = Zachowania zdrowotne studentów – badania własne - Weber-Rajek, Magdalena; Baumgart, Mariusz; Michalski, Adam; Radzimińska, Agnieszka; Goch, Aleksander; Lulińska-Kulik, Ewelina; Zukow, Walery (Journal of Education, Health and Sport, 2015)
Weber-Rajek Magdalena, Baumgart Mariusz, Michalski Adam, Radzimińska Agnieszka, Goch Aleksander, Lulińska-Kulik Ewelina, Zukow Walery. Students’ health behaviors – own research = Zachowania zdrowotne studentów – badania własne. Journal of Education, Health and Sport. 2015;5(9):647-662. ISSN 2391-8306. DOI10.5281/zenodo.31757 http://dx.doi.org/10.5281/zenodo.31757 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%289%29%3A647-662 https://pbn.nauka.gov.pl/works/642067 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.08.2015. Revised 05.09.2015. Accepted: 29.09.2015. Students’ health behaviors – own research Zachowania zdrowotne studentów – badania własne Magdalena Weber-Rajek1, Mariusz Baumgart2, Adam Michalski3, Agnieszka Radzimińska1, Aleksander Goch1, Ewelina Lulińska-Kulik3, Walery Zukow4 1. Uniwersytet Mikołaja Kopernika w Toruniu Collegium Medicum w Bydgoszczy Katedra Fizjoterapii, Bydgoszcz, Polska / Nicolaus Copernicus University in Toruń, Collegium Medicum in Bydgoszcz, Department of Physiotherapy, Bydgoszcz, Poland 2. Uniwersytet Mikołaja Kopernika w Toruniu, Collegium Medicum w Bydgoszczy, Katedra i Zakład Anatomii Prawidłowej, Bydgoszcz, Polska / Nicolaus Copernicus University in Toruń, Collegium Medicum in Bydgoszcz, Department of Anatomy, Bydgoszcz, Poland 3. Bydgoska Szkoła Wyższa, Bydgoszcz, Polska / University of Bydgoszcz, Bydgoszcz, Poland 4. Uniwersytet Kazimierza Wielkiego, Bydgoszcz, Polska / Kazimierz Wielki University, Bydgoszcz, Poland Summary Introduction Life style is the main health determiner. Early adulthood is the best period for achieving long-term advantages by choosing healthy life style. However, the results of the research concerning health behaviours of the young people done in Poland and in the world are not satisfactory. The aim of the study The aim of the research paper was to evaluate health behaviors among the young people studying on various courses at one of the universities in Bydgoszcz. The aim of the research was also to state whether there is any difference between health behaviors of the students studying on medical courses and non-medical ones and whether there is a difference in health behaviours among women and men. Material and Methods 150 students (82 women and 68 men) from the University of Bydgoszcz studying: Physiotherapy, Dietetics and Logistics were examined. The research was done with use the Inventory of Health Behavior (IoHB) by Juczyński. Statistical analysis was done with the package PQStat package version 1.4.8. Results An average IoHB result for the entire examined group amounts to 6.96 sten which forms the border between results medium and high. The best IoHB questionnaire results were obtained in the category “proper nutrition habits”, the worst in the category “health practices”. Conclusions There is a need for further research concerning health habits among the young people and dissemination of health promotion programs at all educational levels. Key words: health behaviors, students. Streszczenie Wstęp Styl życia jest głównym determinantem zdrowia. Wczesna dorosłość jest najlepszym okresem dla osiągnięcia długotrwałych korzyści z wyboru zdrowego trybu życia. Jednakże wyniki badań dotyczących zachowań zdrowotnych młodzieży prowadzonych w Polsce i na świecie nie są zadawalające. Cel badań Celem pracy była ocena zachowań zdrowotnych młodzieży studiującej w jednej z bydgoskich szkół wyższych na różnych kierunkach studiów. Badania miały także na celu określenie, czy istnieje różnica w zachowaniach zdrowotnych studentów studiujących na kierunkach medycznych i niemedycznych oraz czy istnieje różnica w zachowaniach zdrowotnych między kobietami i mężczyznami. Materiał i Metody Badaniami objęto 150 studentów (82 kobiety i 68 mężczyzn) z Bydgoskiej Szkoły Wyższej studiujących na kierunkach: Fizjoterapia, Dietetyka i Logistyka. Do badań wykorzystano Inwentarz zachowań zdrowotnych (IZZ) Zygfryda Juczyńskiego. Analizę statystyczną przeprowadzono wykorzystując pakiet PQStat wersja 1.4.8. Wyniki Średni wynik kwestionariusza IZZ dla całej badanej grupy wynosi 6,96 sten, co stanowi granicę między wynikami średnimi i wysokimi. Najlepsze wyniki kwestionariusza IZZ uzyskali studenci Dietetyki, najgorsze studenci Logistyki. W całej badanej grupie najlepsze wyniki uzyskano kategorii „prawidłowe nawyki żywieniowe”, najgorsze w kategorii „praktyki zdrowotne”. Wnioski Istnieje potrzeba dalszych badań zachowań zdrowotnych młodzieży i upowszechniania programów promocji zdrowia na wszystkich etapach edukacji. Słowa kluczowe: zachowania zdrowotne, studenci.